2017
DOI: 10.1002/adfm.201703014
|View full text |Cite|
|
Sign up to set email alerts
|

3D Electrophoresis‐Assisted Lithography (3DEAL): 3D Molecular Printing to Create Functional Patterns and Anisotropic Hydrogels

Abstract: The ability to easily generate anisotropic hydrogel environments made from functional molecules with microscale resolution is an exciting possibility for the biomaterials community. This study reports a novel 3D electrophoresis-assisted lithography (3DEAL) platform that combines elements from proteomics, biotechnology, and microfabrication to print well-defined 3D molecular patterns within hydrogels. The potential of the 3DEAL platform is assessed by patterning immunoglobulin G, fibronectin, and elastin within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Chitosan has demonstrated potential in cartilage and bone tissue engineering since it can support the expression of ECM proteins in chondrocytes and osteoblasts, and accelerate vascularization to induce intramembranous bone formation. , Although injectable chitosan-based hydrogels and chitosan/bioceramic composited hydrogels are effective strategies to repair small focal cartilage or bone defects, they show little effect on the repair of large osteochondral defects due to mechanical insufficiency. Multilayered/gradient hydrogels are developed by assembling hydrogels with varying compositions and structures. These can imitate the layered mechanical and biomedical functions of osteochondral tissue. , For chitosan-based hydrogels, the mechanical weakness hinders their fabrications to achieve the gradient, osteochondral-mimicking characteristics, and fulfill the load-bearing functions. The chitosan hydrogels prepared from the LiOH/urea solvent system were biocompatible, tough, and robust, which have promising applications in load-bearing tissue engineering, but there have been very limited studies reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan has demonstrated potential in cartilage and bone tissue engineering since it can support the expression of ECM proteins in chondrocytes and osteoblasts, and accelerate vascularization to induce intramembranous bone formation. , Although injectable chitosan-based hydrogels and chitosan/bioceramic composited hydrogels are effective strategies to repair small focal cartilage or bone defects, they show little effect on the repair of large osteochondral defects due to mechanical insufficiency. Multilayered/gradient hydrogels are developed by assembling hydrogels with varying compositions and structures. These can imitate the layered mechanical and biomedical functions of osteochondral tissue. , For chitosan-based hydrogels, the mechanical weakness hinders their fabrications to achieve the gradient, osteochondral-mimicking characteristics, and fulfill the load-bearing functions. The chitosan hydrogels prepared from the LiOH/urea solvent system were biocompatible, tough, and robust, which have promising applications in load-bearing tissue engineering, but there have been very limited studies reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The use of electrophoresis to generate patterns within hydrogels has been demonstrated previously; Dai et al [43] used an electric field to drive charged molecules through holes in a glass or plastic mask, which created patterned columns within a hydrogel. Aguilar et al [44] improved this method by using a mask material that was permeable to ions and water, minimizing the impact of the mask on the electric field and enabling patterns to be created through centimeters of hydrogel material. Another method relies on patterning the electrode itself in lieu of creating a mask [45], although this method has only been demonstrated with patterning of copper ions.…”
Section: Introductionmentioning
confidence: 99%
“…Progress in the cell culture and tissue engineering fields requires the design of novel functional biomaterials, in particular three-dimensional (3D) scaffolds. Hydrogels, which are highly hydrated materials, have come to the forefront in the design of such scaffolds, which need to be biocompatible, mechanically tunable, and offer opportunity for biofunctionalization. A variety of natural and synthetic molecular building blocks can be found in the literature that allows the design of such hydrogels.…”
Section: Introductionmentioning
confidence: 99%